'Out-of-the-Box' Hinduism: Double Diaspora and the Guyanese Hindus of Queens, NY. (24th December 2018) - Thomases, Drew; Reich, James D
Abstract: New York City is home to a thriving immigrant community of Guyanese Hindus. Descended from indentured laborers who left India in the 19th and early 20th centuries, these Hindus moved again to New York in the second half of the 20th century. They have roots in both India and Guyana, and are thus in a position of "double diaspora." In New York, they now have many more opportunities to meet and interact with recent Indian immigrants in their new home. This paper examines how members of this religious community understand themselves and their relationship with their own past and future, how they think and feel about India and the Indians that they meet in New York, and how their situation of double diaspora shapes both their anxieties and their hopes for their community.